2020
DOI: 10.3892/mmr.2020.11110
|View full text |Cite
|
Sign up to set email alerts
|

miR‑10a‑5p inhibits osteogenic differentiation of bone marrow‑derived mesenchymal stem cells

Abstract: The use of human bone marrow mesenchymal stem cells (hBMScs) as a tissue engineering application for individuals affected by osteoporosis and other types of bone loss diseases has been well studied in recent years. The osteogenic differentiation of hBMScs can be regulated by a number of cues. Micrornas (mirnas/mirs) serve as the key regulators of various biological processes; however, to the best of our knowledge, no information exists with regards to the specific modulatory effects of mir-10a-5p on osteogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Bioinformatics analysis suggested that lncPVT1 promoted the osteoblast differentiation of PDLCs by binding to miR‐10a‐5p, which is involved in cell proliferation, 38 apoptosis, 39 and the progression of osteoarthritis and cancers 40,41 . A previous study showed that miR‐10a‐5p could inhibit the osteogenic differentiation of bone mesenchymal stem cells (BMSCs) 42 . Here, we revealed the binding potential of lncPVT1 and miR‐10a‐5p using the RIP assay.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Bioinformatics analysis suggested that lncPVT1 promoted the osteoblast differentiation of PDLCs by binding to miR‐10a‐5p, which is involved in cell proliferation, 38 apoptosis, 39 and the progression of osteoarthritis and cancers 40,41 . A previous study showed that miR‐10a‐5p could inhibit the osteogenic differentiation of bone mesenchymal stem cells (BMSCs) 42 . Here, we revealed the binding potential of lncPVT1 and miR‐10a‐5p using the RIP assay.…”
Section: Discussionmentioning
confidence: 85%
“…40,41 A previous study showed that miR-10a-5p could inhibit the osteogenic differentiation of bone mesenchymal stem cells (BMSCs). 42 Here, we revealed the binding potential of lncPVT1 and miR-10a-5p using the RIP assay. Besides, miR-10a-5p was significantly downregulated during osteogenesis and negatively correlated with the expression level of lncPVT1.…”
Section: Discussionmentioning
confidence: 96%
“…In vitro experiments, miRNA-10a-5p played a negative regulatory role in the osteogenic differentiation of human bone marrow MSCs by targeting ALP and RUNX2 genes. Similarly, in vivo miRNA-10a-5p negatively regulated the osteogenic differentiation of human bone marrow mesenchymal stem cells [ 30 ]. In our study, the effect of miRNA-10a-5p on chicken myoblasts’ differentiation was similar to that described above.…”
Section: Discussionmentioning
confidence: 99%
“…As determined by transcriptome and multi-omics sequencing technologies, AT-MSC-Exos are enriched with bioactive molecules (microRNAs (miRNAs), enzymes, cytokines, chemokines, immunoregulatory, trophic, and growth factors), that are responsible for AT-MSC-Exo-dependent beneficial effects in inflamed and injured neural and retinal tissues (Table 1) [20][21][22][23][24][25][26][27].…”
Section: Molecular Mechanisms Responsible For the Beneficial Effects ...mentioning
confidence: 99%